Cytomegalovirus infection after kidney transplantation - Scheffel, Thamiris Becker; Schroeder, Regina Barbosa; Keitel, Elizete; Neumann, Jorge Milton; Weber, Liliana Portal (Brazilian Journal of Transplantation, 2015)
Kidney transplantation is the most frequently transplantation globally. carried out. However, although kidney transplants have in most cases positive results, the continuing use of immunosuppressive drugs could pose a negative impact on the patient, leaving him susceptible to infectious complications. A major complication is the cytomegalovirus infection that occurs mainly in the first three months after transplantation, an important morbidity and mortality cause in those patients. Currently, to reduce the risk of cytomegalovirus disease there are two therapeutic strategies: preemptive therapy and prophylaxis. However, despite the therapeutic protocols are established, viral resistance and relapse of the cytomegalovirus disease have put them again in debate. In this context, the aim of the study is to perform a narrative review on the cytomegalovirus infection in kidney transplant, addressing the viral characteristics in the development of the cytomegalovirus infection and disease, as well as the risk factors and impact on the patient, the preference for the antigenemia pp65 method or the use of nucleic acid testing (NAT) for the diagnosis and current treatment strategies. For this review, the databases were consulted, being selected current articles with relevant matter to the subject.